1996
DOI: 10.1073/pnas.93.4.1423
|View full text |Cite
|
Sign up to set email alerts
|

Localization of 17beta-hydroxysteroid dehydrogenase and characterization of testosterone in the brain of the male frog.

Abstract: Several enzymes involved in the formation of steroids of the pregnene and pregnane series have been identified in the brain, but the biosynthesis of testosterone has never been reported in the central nervous system. In the present study, we have investigated the distribution and bioactivity of 17j8-hydroxysteroid dehydrogenase (1713-HSD) (EC 1.1.1.62; a key enzyme that is required for the formation of testosterone and estradiol) in the brain of the male frog Rana ridibunda. By using an antiserum against human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…Previously, the presence of type 1 17 -HSD primarily catalyzing the interconversion of E1 and E2 with a predominance of the reductive pathway was demonstrated in the rat, frog and human fetal brain using immunocytochemical techniques (Milewich et al 1990, Pelletier et al 1995, Mensah-Nyagan et al 1996. We found that also in the human temporal lobe 17 -HSD type 1 is expressed with mRNA concentrations about 10 000-fold lower than in the placenta.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, the presence of type 1 17 -HSD primarily catalyzing the interconversion of E1 and E2 with a predominance of the reductive pathway was demonstrated in the rat, frog and human fetal brain using immunocytochemical techniques (Milewich et al 1990, Pelletier et al 1995, Mensah-Nyagan et al 1996. We found that also in the human temporal lobe 17 -HSD type 1 is expressed with mRNA concentrations about 10 000-fold lower than in the placenta.…”
Section: Discussionmentioning
confidence: 90%
“…However, recent studies indicate that non-gonadal tissues can produce sex steroids and sex-steroid precursors (Labrie et al 1995;Mensah-Nyagan et al 1996;Baulieu 1998;Schlinger et al 1999), and these non-gonadal steroids could support winter territoriality. The adrenals can secrete androgen precursors in several species, perhaps including birds (Schlinger et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Other enzymes, such as 3␤-hydroxysteroid dehydrogenase͞⌬ 5 -⌬ 4 -isomerase (3␤-HSD) and 17␤-HSD, also are expressed in the amphibian brain and are involved in the conversion of pregnenolone to progesterone, androstenedione, and testosterone (8,10,11).…”
mentioning
confidence: 99%